How did Covid-19 pandemic affect the risk of a crisis in the USA - Linhart, Lukáš; de Batz de Trenquelléon, Laure Sabine Marie; Zezula, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis provides a relevant and up-to-date analysis of the COVID-19 impacts on the U.S. economy. In conclusion, the findings suggest that COVID-19 has had an impact on the risk of a crisis in the U.S. as indicated by the results of the EWS used in this thesis. The system identified an increased risk of a crisis in the observed period which highlights the importance of monitoring important indicators in real-time to detect risks and mitigate crises.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses